Pengembangan Standar dan Kualitas Kompetensi Guru Profesional Melalui Program Sertifikasi di Era Revolusi Industri 4.0 - Asyarah, Wulan Noviyanti; Wulandari, Febriana; Primasti3, Yeni Dyan; Wijaya, Hendera; Warman, Warman (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Teachers have a very important role in forming a quality future generation. Standard and quality point values must be tested so that the certification program can run well. However, in the Era of the Industrial Revolution 4.0, there are triggers for teachers, some of whom have not behaved appropriately in the certification program given directly by the government. Judging from the experience of developed countries, it shows that a country, even with minimal natural resources, can become a developed country because it is supported by quality human resources. Therefore, teachers are a solid foundation in creating the progress of a nation. The purpose of this research as a description of the development of standards and quality of teacher professional competence through certification programs, especially in the Era of Revolution 4.0. Because the certification program is a form of recognition from the government where teachers are recognized for their professional duties. This research approach is a literature study with a descriptive research type. Data analysis techniques are obtained through. The research results show that there are three stages in developing teacher professionalism competencies in facing certification, namely 1). Teacher Competence, 2) Teacher professionalism, 3) Implementation 4) monitoring and evaluation stages. Apart from that, there is the development of teacher competency standards through certification programs in the Era of Revolution 4.0. including 1) Technology Integration), and 2) Project and collaboration based learning. 3). 4C skills (Creativity, critical thinking, communication and collaboration) 4). Inclusive and Differentiated Education, 5). Performance and project based evaluation.